Collisional trap losses of cold, magnetically-trapped Br atoms - Lam, J; Rennick, C; Softley, T (American Physical Society, 2014)
Near-threshold photodissociation of Br$_2$ from a supersonic beam produces slow bromine atoms that are trapped in the magnetic field minimum formed between two opposing permanent magnets. Here, we quantify the dominant trap loss rate due to collisions with two sources of residual gas: the background limited by the vacuum chamber base pressure, and the carrier gas during the supersonic gas pulse. The loss rate due to collisions with residual Ar in the background follows pseudo first-order kinetics, and the bimolecular rate coefficient for collisional loss from the trap is determined by measurement of this rate as a function of the background Ar pressure. This rate coefficient is smaller than the total elastic collision rate coefficient, as it only samples those collisions that lead to trap loss, and is determined to be $\langleνσ\rangle = (1.12±0.09)×10^{-9}\,\text{cm}^3\, \text{s}^{-1}$. The calculated differential cross section can be used with this value to estimate a trap depth of $293±24\,\text{mK}$. Carrier gas collisions occur only during the tail of the supersonic beam pulse. Using the differential cross section verified by the background-gas collision measurements provides an estimate of the peak molecular beam density of $(3.0±0.3)×10^{13}\,\text{cm}^{-3}$ in good agreement with the prediction of a simple supersonic expansion model. Finally, we estimate the trap loss rate due to Majorana transitions to be negligible, owing to the relatively large trapped-atom phase-space volume.